Preparation and in vivo evaluation of a gel-based nasal delivery system for risperidone - Gu Fugen; Ma Weina; Meng Gendalai; Wu Chunzhi; Wang Yi (Acta Pharmaceutica)
The aim of this study was to prepare a nasal gel of risperidone and to investigate the pharmacokinetics and relative bioavailability of the drug in rats. Compared with oral dosing, the risperidone nasal gel exhibited very fast absorption and high bioavailability. Maximal plasma concentration (cmax) and the time to reach cmax (tmax) were 15.2 μg mL-1 and 5 min for the nasal gel, 3.6 μg mL-1 and 30 min for the oral drug suspension, respectively. Pharmacokinetic parameters such as tmax′, cmax and AUC of oral and nasal routes were significantly different (p < 0.01). Relative bioavailability of the drug nasal preparation to the oral suspension was up to 1600.0 %. Further, the in vitro effect of the risperidone nasal gel on nasal mucociliary movement was also investigated using a toad palate model. The risperidone nasal formulation showed mild ciliotoxicity, but the adverse effect was temporary and reversible.